Maryse Condé’s Heremakhonon As a Noir Novel - Irina Dzero (Studies in 20th & 21st Century Literature, 2015)
A noir genre analysis of Heremakhonon explains the confusion, sensuality, red herrings, and flashbacks that permeate the novel, as well as the primacy of an investigation to the plot. Upon arriving in a newly independent West African country, protagonist Veronica witnesses the arrest of a political activist who opposed the ruling elite. When she investigates his disappearance, Veronica realizes that she is complicit with the elite perpetrators.
Keywords: noir; postcolonial; West Africa; interiorized racism; Guadeloupe; Maryse Condé; Heremakhonon; En attendant le bonheur; Waiting for Happiness